Technology Entrepreneurship Project (ENT 600) : Step Tracker Sports Shoes / Iskandar Zulkarnain Dali - Dali, Iskandar Zulkarnain; Pagang, Janet Linda; Jilihi, Khairol Ikhwan; Mohd Affendy, Khairulnizam; Ghani, Nur Ikmalia; Mohammad Zaidi, Widad Zunnurain (2021)
New product development is the process of which bringing a new product or the product innovations that created to promote to the market. This will include some steps whereby the product must be completed before it can be launched and promote to the market. Thus, in New Product Development (NPD) report, we came out with a solution to the problem of the customer which by developing a new product as Step Tracker Sports Shoes and the product was actually considered as improvement to existing product. The Step Tracker Sports Shoes was designed with many benefits followed up by the current trends. This sports shoes will be used to detect the step of the person when they are running. Besides, these shoes can help to measure the pace of the running so the runner could easily archieved their target and also maintain their fitness. Other than that, these sports shoes can help to prevent from injuries that might occur as the shoes was created with special features and abilities such as foot landing, cadence, balance and time on the ground, metrics which you cannot get from wrist based trackers. In this report, there were more depth details and description that mentioned about this Step Tracker Sports Shoes that can be clearly seen in each and every section.